INCREASING STUDENTS’ MOTIVATION ON LEARNING WRITING SKILLS THROUGH INQUIRY APPROACH - Sitti Hamsina (Universitas Islam Negeri Alauddin Makassar, 2020)
This present study investigated students’ motivation for learning writing skills through an inquiry approach. The research methodology that was used the type of descriptive research using correlational, where the researchers wanted to know the motivation of students as well as see differences in student motivation in learning writing skills through an inquiry approach. This study used purposive sampling and the respondents were the tenth-grade students of MAN 3 Makassar consist of two classes. They are the 10th Science grade that used the inquiry approach and the 10th Social grade with a non-inquiry approach consists of 30 students in each class. Collecting data in this study used a close question by using the MSLQ. Then to analyze the data, the present researcher used a paired samples t-test by using SPSS 22 for windows. Based on the data analysis, the present researcher found that the mean score of and the 10th Science grade for three motivation scales namely: control belief (5.76), self-efficacy (5.68), and anxiety (5.46) and the 10th Social grade got control belief (5.18), self-efficacy (5.14), and anxiety (4.99). The interpretation scale of the three motivation scales of the 10th Science grade obtained a mean score higher than the 10th Social grade. The t-scores of the three scales, two of them of control belief scale and self-efficacy scale were a significant difference at 0.05 level and the anxiety scale was not a significant difference. The present researcher states that the inquiry learning approach could increase students’ motivation for learning writing skills for the tenth grade of MAN. Based on the results of this study, researchers currently expect that English teachers could use the inquiry learning approach to teach English writing skills.